Case report: Hepatocellular carcinoma in a patient with Pyridoxamine 5-phosphate oxidase (PNPO) deficiency undergoing pyridoxal 5-phosphate (PLP) treatment - Lee, Jesse Zhen Cheng; Chow, Chit Kwong; Fung, Cheuk-Wing; Lui, Stephen Tak Yau; Wong, Suet-Na Sheila (Molecular genetics and metabolism reports, 2025)
Pyridoxamine 5-phosphate oxidase (PNPO) deficiency is an autosomal recessive inborn error of metabolism that typically manifests as seizures resistant to conventional anticonvulsants, often presenting in the neonatal period to early infancy. One of the main treatments, pyridoxal 5-phosphate (PLP), carry a risk of liver toxicity. Concerns about liver toxicity have emerged not only with high doses of PLP but also with lower doses, prompting further investigation into the relationship between PLP treatment and liver complications in patients with PNPO deficiency. This report presents the first case report of hepatocellular carcinoma (HCC) in a patient with PNPO deficiency receiving PLP Pyridoxamine 5-phosphate oxidase (PNPO), identified before reaching teenager. This case underscores the importance of regular liver function monitoring for patients on long-term PLP therapy, suggesting a potential association between PLP treatment and the development of HCC, which has significant implications for clinical management strategies. •Links PLP to HCC in PNPO deficiency.•Liver toxicity can occur at any dose.•Start with lower PN doses to reduce risk.•Monitor LFT and AFP regularly.•Adjust medications early to prevent complications.